2018
DOI: 10.1002/clen.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emission During Composting and Vermicomposting of Organic Wastes – A Review

Abstract: Human‐induced climate change, mainly through greenhouse gases emission (GGE), is attracting attention worldwide and has become one of the major threats to the environmental sustainability. Utmost is the need to understand the impact of waste management practices on GGE, or countries could incorporate alternative waste management strategies for various organic wastes. Strict regulatory controls limiting waste disposal in landfills and the consequent diversion of biodegradables have resulted in the adoption of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…After the initial decrease in CO 2 concentration, it increased. This was probably caused by earthworms facilitating the enzymatic and microbial degradation of organic matter resulting in the transformation of wastes into organic humic forms with a significant release of CO 2 [67]. The decrease in CO 2 emissions in week 12 of this study may be attributed to stabilization of the compost as reported by Nada et al [25].…”
Section: Gaseous Emissionssupporting
confidence: 66%
See 1 more Smart Citation
“…After the initial decrease in CO 2 concentration, it increased. This was probably caused by earthworms facilitating the enzymatic and microbial degradation of organic matter resulting in the transformation of wastes into organic humic forms with a significant release of CO 2 [67]. The decrease in CO 2 emissions in week 12 of this study may be attributed to stabilization of the compost as reported by Nada et al [25].…”
Section: Gaseous Emissionssupporting
confidence: 66%
“…The high CH 4 content in week 4 may be attributed to low oxygen concentrations resulting from the relatively high moisture content of the cattle manure substrate in the vermicomposting units compared to the other weeks with measurements ( Table 3). Low oxygen content and high moisture content cause anaerobic conditions in vermicomposting units, hence stimulate the development of methanogenic bacteria that produce CH 4 [66,67]. A reduction in the CH 4 concentration in week 8 and further in week 12 may be attributed to an increase in the earthworm population.…”
Section: Gaseous Emissionsmentioning
confidence: 99%
“…Non-thermophilic biodegradation of organic matter into humus like substances, as a result of feeding earthworms, is referred as vermicomposting (Arancon et al, 2004;Arancon and Edwards 2005;Swati and Hait 2018). During this process organic waste materials pass through the gizzard of earthworms (Ndegwa and Thompson 2001;Hemalatha 2012) and produce vermicast which is rich in essential plant nutrients and unidentified plant growth inducing compounds (Sharma and Garg 2019).…”
Section: What Is Vermicompost?mentioning
confidence: 99%
“…In 2016, 5% of global emissions were generated from solid waste management, excluding transportation. It is estimated that human activities are causing global industrial warming of approximately 1° C, with a weighted margin of 0.8 to 1.2°C [15]. Global warming is likely to reach 1.5° C between 2030 and 2052 if it continues to increase at the current rate [16].…”
Section: Municipal Wastementioning
confidence: 99%